Faktor-Faktor yang Memengaruhi Penawaran Gula Indonesia - Nur Amin; Bayu Krisnamurthi; Dwi Rachmina (Jurnal Agribisnis Indonesia, 2024)
Sugar is a strategic commodity that plays an important role. As the primary sweetener, the use of sugar has not yet been completely replaced by other sweeteners. Another essential role can also be seen in the extent of linkages in downstream industries, such as food and beverage, refined sugar, and pharmaceutical industries. This research aims to analyze what factors influence the supply of sugar and the elasticity of the sugar supply in Indonesia. This research uses secondary data in the form of time series data between 1992-2021. The analytical method that will be used quantitative method. The quantitative method uses a simultaneous equation modeling approach, where each equation is estimated using the Two-Stage Least Square (2SLS) method. Data processing in this research was carried out using the Microsoft Excel 2010 and EViews 12. The research results show that the factors that influence the supply of sugar in Indonesia include the amount of production, imports, exports and Indonesian sugar stocks. The amount of Indonesian sugar production is controlled by sugar-cane production and yield, with positive elasticity. Domestic sugar consumption affects the number of Indonesian sugar imports with positive elasticity, while exchange rate and sugar production affect the number of imports with negative elasticity. Domestic sugar prices affect the amount of Indonesian sugar export with negative elasticity, while GDP have a value positive elasticity. Sugar stock is the identity function of the previous year's sugar supply and the previous year's sugar consumption. The total supply of Indonesian sugar is the identity function of sugar production, sugar imports, sugar exports, and year-end sugar stocks.